Peruvian curanderism, women and culture: a current vision from health anthropology - Huamán Talavera, Ananías Máximo (2024)
Female participation in the field of Curanderism has been a space that transcends the single contemporary reality of this tradition. Over the years, peruvian curanderism has received numerous religious, cultural, and practical influences from various regions of the world. In Peru, female curanderism has represented a health response option in the absence or lack of conventional medical services. This study has been carried out based on the life history of nine healers from different areas of Peru, considering female participation, inclusion and the gender gap in Peruvian curanderism and The analysis presents information that covers the issue of gender, such as the acceptance and healing obtaining of female prestige within curanderism and the inclusion of technological strategies in the curanderism practice.